Survival trends and prognostic factors for patients with extramedullary plasmacytoma: A population-based study - Shen, Xuxing; Zhang, Lina; Wang, Jing; Chen, Lijuan; Liu, Shu; Zhang, Run (Frontiers in Oncology, 2022)
Background: Extramedullary plasmacytoma (EMP) is a localized plasma cell neoplasm that originates from tissues other than bone. The survival trends and prognostic factors of patients with EMP in recent years remain unreported. Methods: We used the SEER databases to extract the data. Survival curves were calculated using the Kaplan-Meier method and a nomogram was created based on the Cox's proportional hazards model. Results: A total of 1676 cases of EMP were identified. Patients in period-2 (2008-2016) show similar survival (p=0.8624) to those in period-1(1975-2007). Age, gender, race, and sites were prognostic of patient outcomes. And the use of surgery was associated with improved survival. The patients were randomly assigned to the training cohort and the validation cohort in a ratio of 2:1. Four factors including age, gender, race, and sites were identified to be independently predictive of the overall survival of patients with EMP. A prognostic model (EMP prognostic index, EMP-PI) comprising these four factors was constructed. Within the training cohort, three risk groups displayed significantly different 10-year survival rates: low-risk (73.0%, [95%CI 66.9-78.2]), intermediate-risk (39.3%, [95%CI 34.3-44.3]), and high-risk (22.6%, [95%CI 15.3-30.9]) (p<0.0001). Three risk groups were confirmed in the internal validation cohort. We also constructed a 5-factor nomogram based on multivariate logistic analyses. Conclusion: The survival of patients with EMP did not improve in recent years. The EMP-PI will facilitate the risk stratification and guide the risk-adapted therapy in patients with EMP.